Processos criativos em direção de arte subsidiados pela fotografia artística no livro do filme - Nóbrega, Helder Paulo Cordeiro da (2021)
This work discusses the creation process in art direction in which we perform this function for the conception of the film Selva (Brasil / Paraíba, HD digital, 120 ’, 2021), by Manoel Fernandes Neto.We understand the creative process as an ordering of ideas (ZAMBONI, 2006) that involve translations and recreation, therefore, a transcreation (CAMPOS, 2011) At the same time, we understand art direction as a restructuring of universes regarding representations of identities such as translations and social and cultural recreations through the construction of the visualities put on the scene. Thus, art direction is structured in the notion of person (MAUSS, 2003), understanding the identity as a social representation (GOFFMAN, 1985) without losing sight of its aspects of social and cultural construction (SILVA, 2000). Given the multiplicity that involves artistic making, towards art, we find in the bricolage, versed by Dias and Irwin (2013) the effective methodological contribution to spell out about our creative process, conceptualized in this study as a book (of the art) of the film, transmedia product, which among other elements uses artistic photography (COTTON, 2010), subject of our clipping, as a subsidy for the construction of space scenic filmic mentioned.